IMPLEMENTASI TRI KAYA PARISUDHA PADA PENGADAAN BARANG UNTUK PENCEGAHAN FRAUD DI ABC RESORT BALI - Priadiarta, Kadek; Wiryanata, IGN Agung; Tuwi, I Wayan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study addresses procurement challenges at ABC Resort, Bali, where price and quantity discrepancies remain prevalent alongside a limited understanding of the application of Tri Kaya Parisudha values in fraud prevention. The research aims to analyze the implementation of manacika (right thought), wacika (right speech), and kayika (right action) within the procurement stages involving the user, Purchasing, and Receiving departments. A descriptive qualitative approach was employed, using interviews, observations, and supporting document analysis such as purchase requests, purchase orders, and receiving reports. The findings reveal that Tri Kaya Parisudha plays a significant role in minimizing potential fraud by enhancing accuracy, fostering honest communication, and ensuring compliance with established procedures. Nevertheless, obstacles such as inconsistent verification and interdepartmental distrust remain. The study concludes that strengthening a work culture rooted in Tri Kaya Parisudha and conducting regular training are essential to reinforce integrity and improve the procurement system.